Peranan Masyarakat Sebagai Penunjang Koordinasi dalam Penyelenggaraan Administrasi di Kantor Kecamatan Watang Sidenreng Kabupaten Sidenreng Rappang - Hasmiani Hasmiani (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Abstract This research was conducted at the District Office of Watang Sidenreng, its purpose was to determine the role of the community as a supporting role of coordination in administration proccess, and all factors that influenced it. Data collection methods used in this research were observation, questionnaires, and literature studies. The collected data were analyzed using frequency tables and percentages. The population was as many as 31 people, and all of them were accounted as sample. The results showed that the role of society in the administration was 100% good. The implementation of coordination in public administration was 100% good. The implementation of coordination in terms of the will to co-operate, increased achievement, respect and passion in work performance were all good by 90,32%. Vertical coordination in each section was 83,87% good. Functional coordination of each section chief to another agency was 77,42% good. Personnel resource in public administration was 51,61% adequate. Administrative services at district office was 70,97% good. The attitude and behavior of employees in public administrative services were 83,87% good. The cooperation among all employees in publilc administrative services was 100% good. Administrative services in terms of service procedure was 58,06% foolproof. The quality of employees in public administrative services was 87,10% qualified. Factors affecting the society’s interaction within public relations officer in public administration were 77,42% good. The existence of community development, fostering citizenship, fostering peace and order assessed 70,97% excellent. It thus becomes a factor that can influence people to take part in supporting the coordination of administration in Watang Sidenreng district.